Thermal energy and mass transport of shear thinning fluid under effects of low to high shear rate viscosity - Mohsan Hassan; Fateh Mebarek-Oudina; Abrar Faisal; Abdul Ghafar; A.I. Ismail (International Journal of Thermofluids, 2022)
The current investigation is deliberated the flow and heat transfer of a shear thinning fluid over a non-linear stretching sheet has variable thickness. All rheological aspects at low to high shear rates are accounted theoretical by using generalized Carreau model of viscosity. Theoretical flow model is formulated for boundary layer phenomena by applying boundary layer approximations and then convert it from partial differential equations to ordinary differential equations with the help of similarity transformations. The solution is obtained by numerical method and the result are displayed in the form of velocity and temperature profiles under impact of rheological and geometrical governing parameters. In addition, the results of skin friction coefficient and Nusselt number are obtained under effects of these parameters. It is found that Nusselt number is significantly decreased when stretching is increased by velocity index parameter.